Continuous lactose fermentation by Clostridium acetobutylicum – Assessment of solventogenic kinetics. (March 2015) - Procentese, Alessandra; Raganati, Francesca; Olivieri, Giuseppe; Russo, Maria Elena; Salatino, Piero; Marzocchella, Antonio
Highlights: Butanol production by ABE fermentation in a CSTR-microfiltration unit is reported. Lactose was adopted as carbon source to mime cheese-whey. Solventogenesis of ABE fermentation was characterized under steady state conditions. A product inhibition model was adopted for the butanol production rate. Abstract: This work reports the results of a series of tests on the specific butanol production rate by Clostridium acetobutylicum continuous cultures. The tests were carried out using lactose as carbon source to mimic cheese-whey. A continuous stirred tank reactor equipped with a microfiltration unit was used. The dilution rate ( D ) ranged between 0.02 and 0.15 h −1 and the ratio R of the permeate stream rate to the stream fed to the reactor ranged between 14% and 95%. For each set of D and R values, the continuous cultures were characterized in terms of concentration of cells, acids and solvents. Results were processed to assess the concentration of acidogenic cells, solventogenic cells, spores and the specific butanol production rate. The max butanol productivity was 0.5 g L −1  h −1 at D  = 0.1 h −1 and R  = 95%. The butanol productivity referred to solventogenic cells was expressed as a function of concentration of lactose, acids and butanol.